Honor roll, the following patriotic men and women in this organization have invested in the Victory Liberty Loan. (Regensteiner Colortype Co., 1919)
The poster depicts a flag with a blue "V" on white field with a wide red border, and, under the text, spaces numbered 1 to 100 for listing bond purchasers.